Virtual reality can combat isolation with awe and empathy — on Earth and in space - Stepanova, Katerina (The Conversation, 2021)
Stay-at-home and quarantining orders have led to increasing isolation. Virtual reality may help alleviate some of the negative feelings of isolation, and this has potential implications for space travel.
Keywords: Riecke_2021; dissemination-4generalPublic; katerina-stepanova; mediaCoverage; proj--sirius; thesis-related